Evaluation of the Patients’ and Physicians’ Satisfaction with Efficacy of Protact Mouthwash for Oral Ulcer and Aphthous - Fatemeh Mirzaee; Mahmood Moosazadeh; Seyed Jalal Hosseinimehr (Journal of Mazandaran University of Medical Sciences)
Background and purpose: Aphthous and oral ulcers are the most common ulcerative conditions of the oral mucosa, presenting as painful sores on the oral or tongue mucous membranes that make eating and drinking difficult. Zataria multiflora Boiss. has demonstrated therapeutic potential and has been used in formulations such as Protact® mouthwash. Recent studies indicate that this plant possesses several therapeutic effects, including alleviating inflammation and promoting healing in oral, digestive, and skin wounds. Given the documented effectiveness of this plant in treating various types of oral wounds and inflammation, along with the availability of Protact® mouthwash in pharmacies nationwide, this study aims to evaluate patient and physician satisfaction with the efficacy of Protact® mouthwash for treating oral ulcers and aphthous ulcers in Sari and Babol, the two largest cities by population in Mazandaran province. Materials and methods: This descriptive, cross-sectional study included a sample of 75 individuals, consisting of 35 physicians and 40 patients from Sari and Babol who either prescribed or used Protact® mouthwash. A convenience sampling method was used, with participants selected based on their willingness to complete a checklist. Data were collected by trained interviewers visiting medical centers, physician clinics, and pharmacies, and inviting participants to complete the checklist. Data were presented as mean ± standard deviation (M ± SD), percentages, median, minimum, and maximum values. Statistical analysis was performed using chi-squared, Kolmogorov–Smirnov, and independent t-tests. Results: The majority of participants in both groups were men (patients: 52.5%, or 21 out of 40; physicians: 94.3%, or 33 out of 35). The mean, median, standard deviation, minimum, and maximum ages for physicians were 53.94, 56, 7.6, 40, and 68 years, respectively, while those for patients were 40.13, 42, 10.8, 18, and 63 years, respectively. Most patients in this study (75%) reported a high level of satisfaction after using Protact® mouthwash. This mouthwash was mainly used for the treatment of aphthous stomatitis and oral inflammation, with a frequency of 52.5%. Results from the physicians' checklists showed that Protact® mouthwash was most frequently prescribed by dentists (42.9%), followed by general practitioners, hematologists and oncologists, and radiologists (each with a frequency of 11.4%). Additionally, physicians expressed satisfaction with the healing progress in their patients. Conclusion: The findings support the effectiveness of Protact® mouthwash, a natural product produced in Iran, for the prevention and treatment of oral cavity-related conditions. The efficacy of this product is likely attributed to the presence of major phytochemicals in Zataria multiflora extract and essential oil, including thymol and carvacrol, which possess anti-inflammatory, antioxidant, antimicrobial, and tissue-regenerative properties beneficial to mucosal and skin healing.